METHODS OF AUTOMATIC DEVELOPMENT OF ELF LEARNERS’ VOCABULARY IN A DIGITAL LEARNING ENVIRONMENT (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This study investigates the methods of automatic development of English as a Lingua Franca (ELF) learners’ vocabulary within digital learning environments. With the growing presence of technology in language education, digital platforms and AI assisted tools have become essential in facilitating vocabulary acquisition. The paper explores how automatic methods, including adaptive learning systems, intelligent tutoring platforms, and AI powered lexical exercises, enhance learners’ exposure to diverse vocabulary, support contextual understanding, and promote retention. Special attention is given to how these methods allow learners to practice vocabulary in communicative, task based scenarios that reflect real ELF interactions. The study also discusses practical strategies for integrating automated vocabulary development tools in classroom and online settings, highlighting both benefits and challenges. Findings suggest that automatic vocabulary development methods in digital environments significantly improve learners’ lexical competence, autonomy, and readiness for authentic ELF communication.